In-situ decomposition of sugarcane trash using microbial consortium and its impact on ratoon cane - Sugumaran , M P; Gayathry, G; Porkodi, G; Kalaiselvi , P; Kiruba, M; Sassikumar , D; Natarajan , K; Bharathi , K K (Plant Science Today, 2025)
Sugarcane trash, consisting of leaves and stalk residues left after harvesting, poses challenges such as slow decomposition, nutrient imbalance and environmental concerns. This study explores an eco-friendly approach to sugarcane trash management using a microbial consortium to accelerate decomposition and improve soil health and ratoon cane yield. These microorganisms facilitate sugarcane trash decomposition by reducing the C: N ratio and breaking down lignocellulosic compounds. Applying a trash decomposer at 30 kg/ha on the 3rd, 15th and 30th days after harvest, along with 100% RDF fertilizers, significantly reduced sugarcane trashs’ C: N ratio to 18.25 by the 60th day. This treatment also improved growth and yield parameters in the ratoon crop. FTIR analysis confirmed compost maturity, shifting from aliphatic to aromatic compounds. The nitrate band at 1384 per cm intensified, while peak ratio changes indicated intensified decomposition progress of the trash. A higher proportion of cellulose-degrading consortia in trash D promoted the breakdown of complex molecules and reduced humification during in-situ decomposition. The findings suggest that integrating microbial decomposition strategies with lignocellulosic residues could enhance soil fertility, thus enhancing nutrient availability.